Pendekatan Tematik-Holistik sebagai Model Transformasi Hukum Islam: Analisis Naṣṣ Wali Nikah - Mukhammad Khabibulloh Idris (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
The Qur’an and Hadith do not define marriage guardianship (wali nikah) in a single explicit rule, but present it through verses and narrations emphasizing protection, justice, and women’s consent in marriage. Scholarly differences between those who regard guardianship as a pillar of marriage and those who allow limited autonomy for adult women reflect the flexibility of Islamic law in responding to social change. This article examines marriage guardianship through a thematic–holistic approach to reconstruct Islamic family law and ensure its relevance. The thematic approach analyzes relevant verses and hadiths within their specific contexts, while the holistic approach views the texts as an integrated whole oriented toward the objectives of Islamic law (maqāṣid al-sharī‘ah). The findings indicate that guardianship is not absolute authority, but a protective and supportive role, limited by women’s welfare, consent, and the prohibition of coercion, in line with regulations in Indonesia and several Muslim countries.